Load balancing multipath routing protocol for mass remote sensing data downlink in LEO satellite network - Pei-long LIU; Hong-yu CHEN; Song-jie WEI; Hao CHENG; Shuai LI; Jun-yong WANG (Tongxin xuebao)
LEO satellite networks can provide seamless real-time data communication for all kinds of users,which developed rapidly in recent years.At the mean time,the massive payload data down-link system of space data sources,such as remote sensing satellites,still make use of traditional storage and forward mode.The real-time performance of space mission data will be improved effectively,if such satellites are connected to LEO satellite networks equipped with inter satellite links.However,it is necessary to design a specialized satellite network load balancing routing algorithm.Satellite parallel edge-disjoint multipath routing protocol (SPEMR) was designed for remote sensing satellite real-time down-link applications.OPNET simulation results indicate that the performance degradation index(DI) of the multipath scheme implemented by SPEMR is 0.32,which is only 32% of the TLR and 21% of the traditional DSP scheme.It is demonstrated that SPEMR has the better capability of transmitting massive data in real time.